Amar la trama : as narrativas literárias contemporâneas de Jorge Drexler - Lacombe, Michel da Silva Coelho (2024)
The present work aims to analyze the textual work of the Uruguayan composer Jorge Drexler as a look at contemporary times. Based on the lyrics, which, for the study, areconsidered short narratives, we propose to analyze the discussions present in the lyrics and how they resonate in society. For a better observation of contemporaryphenomena, we opted for a temporal cut of his work: the study is focusing onthealbum Eco, published in the period prior to which the artist won the Oscar for best original song (and which culminates with his moving from Montevideo to Madrid), until the then most recent album, Tinta y tiempo, released in 2022. Fromthis study, we find a composer already on a global scale seeking new paths for his compositions without forgetting his South American origin. To understand the intertwiningof themes and the perspectives involved, we decided to study the songs within a larger framework, that is, the album. In this way, it is possible, analogously, to checkthesongs within a larger context, such as a story within a book. With this methodology, it was possible to discuss the creation process within the song's formative spectrumandits connection with literature and the characteristics of the region of its production, that is, Latin America. In the end, it was observed that, even from Europe, the author still has a Latin American perspective and that, even though the civilizational distanceis in place, there are contemporary and common dilemmas, expressed, in his work, infour major themes: movement, identity, belonging and feeling.